2020
DOI: 10.1111/bor.12437
|View full text |Cite
|
Sign up to set email alerts
|

Environmental conditions at the Last Interglacial (Eemian) site Neumark‐Nord 2, Germany inferred from stable isotope analysis of freshwater mollusc opercula

Abstract: Mollusc biogenic carbonates are valuable records of past environmental conditions. In particular, carbonate oxygen (δ18O) and carbon (δ13C) stable isotopes can be used to reconstruct different physical and chemical parameters, according to the different genera used (marine, freshwater or terrestrial). The Last Interglacial (early Eemian) palaeolake of Neumark‐Nord 2 (NN2), Germany provides an excellent example of a Neanderthal archaeological site with abundant freshwater carbonate remains. As in other European… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
2
2
0
Order By: Relevance
“…Data regarding rainfall and temperature during the period of Neanderthal presence at Neumark-Nord 2 come from stable isotope analysis of freshwater mollusk opercula (41) and are in agreement with the results from the oxygen isotope analysis of horse tooth enamel from the Neumark-Nord 2 site (59), which has yielded mean annual temperature estimates for the Last Interglacial. The Mitteldeutsches Trockengebiet in which Neumark-Nord is situated has a mean annual temperature of ~9°C (60) and is in an area of the German "isoscape" with annual average rainfall δ 18 O values between −8.7 and − 9.4 ‰ [see Fig.…”
Section: Vegetation Openness At Neumark-nordsupporting
confidence: 75%
See 2 more Smart Citations
“…Data regarding rainfall and temperature during the period of Neanderthal presence at Neumark-Nord 2 come from stable isotope analysis of freshwater mollusk opercula (41) and are in agreement with the results from the oxygen isotope analysis of horse tooth enamel from the Neumark-Nord 2 site (59), which has yielded mean annual temperature estimates for the Last Interglacial. The Mitteldeutsches Trockengebiet in which Neumark-Nord is situated has a mean annual temperature of ~9°C (60) and is in an area of the German "isoscape" with annual average rainfall δ 18 O values between −8.7 and − 9.4 ‰ [see Fig.…”
Section: Vegetation Openness At Neumark-nordsupporting
confidence: 75%
“…3, (45,(48)(49)(50)]. Our expectation that rainfall and temperature will not differ between sites in the study region is partially confirmed by data from one of the baseline sites, Gröbern, where the temperature history of the Eemian has been reconstructed by palynology and by the bulk carbonate d18O record from that basin (62,63), both methods indicating very similar temperature histories for Gröbern and Neumark-Nord, with temperatures reaching a maximum at both sites during PAZ IVb and remaining stable during PAZ V [see also (41)].…”
Section: Comparison With Other Last Interglacial Sitessupporting
confidence: 60%
See 1 more Smart Citation
“…The Neumark archaeological record contains high-density evidence for flint knapping, animal exploitation and fire use (at NN2) as well as low-density single activity death or kill sites, mostly accumulated during the first 7,000 years of the Eemian. Comprehensive coverage of the Neumark palaeoecological and archaeological studies are assembled in Mania et al (1990), Mania (2010), Meller (2010), Gaudzinski-Windheuser and Roebroeks (2014), Gaudzinski-Windheuser et al (2018) and Kindler et al (2020) (for various detailed studies of a wide range of proxies from Neumark-Nord, see Mania, 2010;Meller, 2010;Bakels, 2012Bakels, , 2014Britton et al, 2012Britton et al, , 2019García-Moreno et al, 2016;Milano et al, 2020).…”
Section: The Visibility Of Hunter-gatherer Activity In Last Interglacial Records At Neumark-nordmentioning
confidence: 99%